Mechanical Circulatory Support in Refractory Vasodilatory Septic Shock: a Randomized Controlled Porcine Study - Chvojka, Jiri; Martinkova, Vendula; Benes, Jan; Valesova, Lenka; Danihel, Vojtěch; Nalos, Lukas; Matejovic, Martin (Shock, 2020)
As controversy persists regarding the benefits of mechanical circulatory support in septic shock with a predominantly vasoplegic phenotype, preclinical studies may provide a useful alternative to fill the actual knowledge gap. Here, we investigated the physiologic responses to venoarterial extracorporeal membrane oxygenation therapy (VA-ECMO) in a clinically relevant porcine peritonitis-induced model of refractory vasodilatory septic shock. In 12 anesthetized, mechanically ventilated, and instrumented domestic pigs, septic shock was induced by intraperitoneally inoculating autologous feces. After reaching the threshold for refractory vasodilatory shock (norepinephrine dose ≥1 μg/kg/min), the pigs were randomized into the conservative treatment group (control) or the VA-ECMO group (target flow 100 mL/kg/min). The time to develop refractory vasodilatory shock was similar in both groups (18.8 h in the ECMO group, 18.1 h in the control group). There was no difference between the groups in terms of time to death measured from the point of reaching the predefined vasopressor threshold (7.1 h for the ECMO group, 7.9 h for the control group). The initiation of ECMO resulted in a markedly increased fluid and vasopressor support. Although treatment with ECMO compromised neither renal nor carotid blood flow initially, both progressively decreased later during the experiment. The pattern of sepsis-induced multiorgan injury, alterations in energy metabolism, and the systemic inflammatory response were remarkably similar between both groups. In conclusion, the application of VA-ECMO in this model of peritonitis-induced refractory vasodilatory septic shock aggravated hemodynamic deterioration. Our findings contribute to increasing equipoise with respect to the clinical utility of VA-ECMO in refractory vasodilatory shock.
Keywords: zánět; Swine; energetický metabolismus; prasata; Energy Metabolism; zvířata; Inflammation; Extracorporeal Membrane Oxygenation; septický šok; Shock, Septic; mimotělní membránová oxygenace; Animals